The role of public spending on infrastructure in supporting agricultural production and achieving food security A cross-sectional study of a States sample for the period 2000-2013 - Benzawi, Mohamed Chrif; Slatni, Hajer (Milev Journal of Research and Studies, 2017)
Through this article the researcher aims to examine the impact of public investment spending in infrastructure on GDP from Agriculture for a sample of European Union countries (Belgium, Portugal, Spain, France, United Kingdom, Greece, Italy, Germany) by relying on Panel Data model in the period from 2000 to 2013. The study found positive and significant impact for the infrastructure of Roads and Maritime infrastructure, and this effect is the same among the sample countries